STUDI DESKRIPTIF PERTUMBUHAN GEREJA SECARA KUALITAS DI GEREJA BETHEL TABERNAKEL KRISTUS ALFA OMEGA TIRTOYOSO - Samuel Silitonga; Gidion Gidion; Rudyanto Chandra (STT Kristus Alfa Omega, 2020)
The church is currently experiencing quality growth. This can be seen from the congregation who is enthusiastic in attending every worship in the church, the congregation presents on time and the congregation consistently comes despite bad weather conditions. Quality growth in this church is also proved by the presence of eight new members who are baptized. This shows that the congregation and the church both want to experience growth together in quality where the church becomes a means for the congregation to be able to grow themselves in a quality manner.